How negative descriptive norms for healthy eating undermine the effects of positive injunctive norms - Staunton, M.; Louis, W.; Smith, J.; Terry, Deborah; McDonald, R. (Wiley-Blackwell Publishing Inc., 2014)
Healthy eating intentions were assessed as a function of theory of planned behavior variables and manipulated group norm salience. Participants (n = 119) were exposed (or not) to a positive injunctive norm that their fellow students approve of eating healthily, and (or not) to a negative descriptive norm that their fellow students do not eat healthily. A significant interaction emerged. When a negative descriptive norm was made salient, participants exposed to a positive injunctive norm reported significantly lower intentions to eat healthily. When no descriptive norm was given, exposure to a positive injunctive norm had no effect. The results suggest the weakness of manipulated injunctive norm salience in the health domain, and the importance of investigating the interactive effects of referent group norms.